The study on the impact of green smartphone purchase intention among academics in the sri lankan higher education sector - Premarathna, P.D.K.D.; Perera, W.P.K.D; Karunarathna, G.C.; Perera, D.T.; Rathnayake, R.M.N.M.; Munasinghe, A.A.S.N. (University of Jaffna, 2022)
Purpose: Due to the serious environmental challenges worldwide, the sustainability of green smartphones has become a crucial societal concern. Therefore, this concept paper empirically observes the impact of green awareness, environmental concern, altruism, and willingness to pay toward green smartphone purchase intention among academics in the Sri Lankan higher education sector. Methodology: The study begins with a quantitative investigation to assess the impact of the independent variables on the dependent variable, followed by a qualitative approach to confirm the validity of the quantitative Findings. The Krejcie and Morgan sampling technique is used to determine 346 respondents from the target population of 3,300 academics in the Sri Lankan Higher Education Sector. In this study, only primary data is used as the main source of information. The study questions are addressed through an anonymous online survey to collect data. Multiple Linear Regression and Content Analysis are performed in the quantitative and qualitative phases respectively. Findings: The literature sources claim to describe the relationships between independent and dependent variables. When referring to prior research, experts have found that most of the Findings regarding the relationship between willingness to pay and intention to buy green smartphones are not favorable. When considering Green Awareness, there is a strong correlation between purchasing intention of green smartphones and Green Awareness. Correspondingly Environmental Concern and Altruism have a favorable effect on buying intentions of smartphones, according to a previous study. So inclusively, past pieces of literature proved most of the independent variables positively impact the dependent variable. Research limitations: The study is only limited to academics in the Sri Lankan Higher Education Sector and concentrates on 346 responses from a 3300 total population of approximately. Mainly, the research focuses on four independent variables. However, there could be different factors that may affect the purchase intention of green smartphones. Implications: The attention of green consumption has been circulating among the general public of Sri Lanka for a longer time, yet such lifestyle adoption has yet to be seen. Public perception to the green concept has thoroughly discussed in many social tiers yet there are many complex barriers for such lifestyle.
Keywords: Green awareness; Altruism; Environmental concern; Willingness to pay; Purchase intention of green smartphones